PENGARUH STRUKTUR MODAL, UKURAN PERUSAHAAN, DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN - Maria Kopa (JURNAL ILMIAH EDUNOMIKA, 2021)
The company has a specific goal by increasing the prosperity of its owners and shareholders through increasing company value. This study aims to determine the effect of capital structure (DER), firm size (total assets) and profitability (ROA) on firm value (PBV). The object of this study is the food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange (BEI) 2015-2019. This study used a purposive sampling method with several specified criteria, and a sample size of 12 companies, and obtained for five years from the annual financial reports, so that a total of 60 company samples. The type of data used in this study is secondary data, where the data obtained from a ready-made form, has been collected and has been processed by other parties in the form of a sample of company annual financial statements. To determine the effect of independent variables on dependent variables, the analysis method used is descriptive statistical test, classical assumptions, multiple regression analysis, hypothesis testing, t test, f test, and analysis of the coefficient of determination using the SPSS program. The results of this study indicate that capital structure has a positive and significant effect on firm value, firm size has a positive and significant effect on firm value, and profitability has a positive and significant effect on firm value.